Who Will Shape the New World Order? - Karl Aiginger (Intereconomics)
Abstract The economic consequences of the war could potentially be used to postpone climate policy, energy saving and the shift to renewable energy. This includes investments in atomic energy — perhaps in smaller plants — as there is still no satisfactory solution for the storage of nuclear waste.